PRODUCTION AND APPLICATION OF KERATINASE ENZYME FROM 4 STRAINS OF BACILLUS SPP. ISOLATED FROM YOGYAKARTA AND GARUT CITY - Wandita, Theresia Galuh (2016)
Recently, chicken feathers have been discarded in bulk as waste from poultry processing industries. Utilization of chicken feathers as sources of protein for animal feed challenge us as an effort to minimize the environmental impact of this waste for creating environmentally friendly farming industry. Chicken feather waste treatment involves the role of the enzyme keratinase through the process of hydrolysis because the chicken feathers containing keratin. Keratinase enzyme can be produced from several microorganisms such as fungi and bacteria. Therefore, enzyme keratinase expected to be produced from Bacillus spp. which has been previously isolated from Yogyakarta and Garut City. The purpose of this research was to determine the production of keratinase enzyme produced from Bacillus spp. and apply the keratinase enzyme in the process of degradation of chicken feathers. Research is consisting of cultivation of Bacillus spp., measuring the growth of Bacillus spp., investigation of degradation of chicken feathers by Bacillus spp., and the production of keratinase enzyme produced by Bacillus spp. Keratinase enzyme production data at varying feather analyzed using completely randomized factorial design 4x2x4 (Completely Randomized Design), and then if there are differences continued with test Duncans New Multiple Range Test (DMRT). This analysis compares the keratinase enzyme produced by each isolate with different types of bacterial isolates are used, the addition of the substrate in the medium, and the difference in incubation time of each isolates of Bacillus spp. From the results obtained bacterial growth and the ability of degradation which is best performed by Bacillus sp. TD5B. The best enzyme production was obtained on medium supplemented with chicken feathers as substrate.